Penguatan Daya Tarik Produk Melalui Kemasan pada UMKM Artaka di Kelurahan Medokan Ayu - Rahma, Tanzalina Aulia; Wardhani, Nuruni Ika Kusuma (Jurnal Ilmiah Wahana Pendidikan, 2024)
Artaka is a Micro, Small and Medium Enterprise (MSME) in the Medokan Ayu Subdistrict area of ​​Surabaya which operates in the fashion sector, namely batik. However, these MSMEs cannot increase sales even though their product types are very diverse, while competition for similar businesses is getting tighter. One of the reasons is that the packaging used is still simple and unattractive, only in the form of ready-to-use brown bags which are widely sold in the market. The aim of preparing this paper is to increase the attractiveness of the product through five stages of activities, namely observation, interviews, documentation, socialization, and creating product packaging designs. Implementation of a new packaging design will increase the attractiveness of the product, attract consumers, expand marketing, and increase sales so that the business can survive and continue to grow.